2017
DOI: 10.13057/biodiv/d180446
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, distribution pattern and microhabitat characteristics of Aglaonema simplex in Pasatan Protected Forest, Jembrana, Bali, Indonesia

Abstract: Lestari D, Asih NPS. 2017. Population structure, distribution pattern and microhabitat characteristics of Aglaonema simplex in Pasatan Protected Forest, Jembrana, Bali, Indonesia. Biodiversitas 18: 1663-1668. Aglaonema simplex Blume is one species of Aglaonema that is distributed in Bali, Indonesia. This species can be found in the forests of Jembrana, Karangasem, Tabanan, Buleleng and Bangli. There is no recent data for A. simplex’s population and microhabitat in Bali, while this data is needed to develop f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Susilowati et al [28] reported that Eurycoma longifolia seedling was distributed in groups and close to the mother plants. Lestari and Asih [29] mentioned that seed spreading agents may affect the distribution of plants, so that clustered plants usually do not have agents to spread the seeds. According to Russo and Augspurger [30] some factors such as seed predators, seed spreading agents and seedling pathogens may affect plant distribution patterns.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…Susilowati et al [28] reported that Eurycoma longifolia seedling was distributed in groups and close to the mother plants. Lestari and Asih [29] mentioned that seed spreading agents may affect the distribution of plants, so that clustered plants usually do not have agents to spread the seeds. According to Russo and Augspurger [30] some factors such as seed predators, seed spreading agents and seedling pathogens may affect plant distribution patterns.…”
Section: Spatial Distributionmentioning
confidence: 99%